ANALYSIS OF TEACHER SERVICE QUALITY ON MINIMAL COMPLETENESS CRITERIA ACHIEVEMENT IN MATHEMATICS LEARNING OF STUDENTS AT SMAN 6 JENEPONTO - Siti Nuralam (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
The study is desciptive quantitative research which aims at analizing teacher service quality and discovering the proritized aspects in improving teacher service quality on KKM (Minimal Completeness Criteria) achievement in Mathematics learning of students at SMAN 6 Jeneponto. The subjects were students in class X with the total of 59 students taken by employing purposive random sampling technique with agreement through the following steps: 1) determining classes as research subject, 2) each of the class was taken with agreement between the research and students who were present when data collection was conducted, students’ presence in class was considered as random presence. The instruments used questionnaire which contained list of questions given to students to rovide description on teacher sevice aligned with their duties and responsibilities in educating, teaching, and training they had experience and expected, and observatin sheet f teachers’ activities aligned with teacher service and the research as observer. Data obtained were analyzed by using descriptive analysis and Importance Performance Analysis (IPA) with importanced the averageof teacher service. The result of the study reveal that 1) the level of students’ satisfication on teacher service in Mathematics learning according to the dimentions of teaching funcion service, teaching function, and training functionis already appropriate with students’ hopes which is in god category. Thus, teacher service quality on KKM achievement in Mathematics learning in class X at SMAN 6 Jenepont is in gd category, 2) there is n dimension to have prioritized in improving teacher service quality in Mathematics learning in class X at SMAN 6 Jenepont n KKM. In general, it can be stated that it has aligned with students’ hopes. However, it is reviewed n each of dimension of teacher service, there are still several attributes that need to be prioritized by teachers. The attribute is in teaching function service dimension, namely attitude in facing students in learning process, learning motivation proviision f students, and teachers’ attention on academic problems experienced by students